Practicum Activity: Analysis of Science Process Skills and Students' Critical Thinking Skills: - Endah Febri Setiya Rini; Febri Tia Aldila (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this study was to determine how the science process and critical thinking skills of VII grade junior high school students were carried out through practicum activities. Methodology: This type of research is qualitative research. The data collection technique used in this research is the interview instrument. The informants in this study came from Batanghari 2 Junior High School, Batanghari 8 Junior High School, and Batanghari 25 Junior High School, with the sample informants being 3 teachers and 6 students. Data analysis techniques use the Miles and Huberman methods. Main Findings: The results of this study are that science teachers in the three schools have implemented practicum activities, and there has been an assessment of science process skills in practicum activities. Students have been trained and assessed for their science process skills and critical thinking skills but have not been trained optimally. Novelty/Originality of this study: The novelty of this research is to analyze practicum activities in improving science process skills and critical thinking skills in three direct schools. Suggestions for further research are finding learning innovations or selecting learning models to improve students' science process skills and critical thinking abilities to make them even better.